Cyberbullying as social labeling in digital identity construction - Aini, Rahmi; Mulyana, Deddy (Jurnal Kajian Komunikasi, 2026)
Background: Cyberbullying has become a prominent feature of digital communication, influencing interpersonal interactions and the ways individuals are perceived and recognized in online spaces. Existing studies have predominantly examined cyberbullying from psychological, educational, and regulatory perspectives, emphasizing its harmful effects and the need for prevention strategies. However, less attention has been given to its role as a communicative process through which social meanings and identity categories are produced, circulated, and legitimized within digital environments. Purpose: This article examines cyberbullying as a process of social labeling and explores its contribution to digital identity construction. Methods: A qualitative conceptual approach was employed through theoretical analysis and interpretive synthesis of scholarly literature and illustrative cases. The analysis integrates labeling theory, symbolic interactionism, and digital communication theory to explain how identity is shaped through online interactions. Results: Cyberbullying operates through interconnected processes of symbolic labeling, audience participation, discursive repetition, and algorithmic amplification. These mechanisms transform isolated negative evaluations into enduring identity narratives, thereby strengthening both primary and secondary labeling. The persistence and visibility of digital communication further intensify the formation of stigma and influence identity negotiations. Conclusion: Cyberbullying extends beyond online aggression and functions as a socio-communicative process through which identities are framed, reproduced, and stabilized in networked publics. Implications: A triadic model linking communicative interaction, algorithmic amplification, and identity internalization is proposed to explain how cyberbullying shapes digital identity, offering a communication-based framework for future research and digital literacy initiatives.